1992
DOI: 10.1073/pnas.89.9.3800
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of "injurin," an inducer of expression of the gene for hepatocyte growth factor.

Abstract: The marked and rapid increase of hepatocyte growth factor (HGF) mRNA in the intact lung of rats after partial hepatectomy or unilateral nephrectomy suggests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(60 citation statements)
references
References 37 publications
3
57
0
Order By: Relevance
“…In this regard, we found in the present study that the level of REG IV expression showed significant positive correlations with those of bFGF and HGF, although the REG IV gene is expressed in colonic epithelial cells while bFGF and HGF are produced mainly by interstitial mesenchymal cells. [23][24][25][26] These findings may indicate the presence of mutual interaction between growth factors in the epithelium and those in the interstitial cells.…”
Section: Effects Of Reg IVmentioning
confidence: 88%
“…In this regard, we found in the present study that the level of REG IV expression showed significant positive correlations with those of bFGF and HGF, although the REG IV gene is expressed in colonic epithelial cells while bFGF and HGF are produced mainly by interstitial mesenchymal cells. [23][24][25][26] These findings may indicate the presence of mutual interaction between growth factors in the epithelium and those in the interstitial cells.…”
Section: Effects Of Reg IVmentioning
confidence: 88%
“…It is regulated during development (DeFrances et al, 1992;Sonnenberg et al, 1993), and by hormones and cytokines (Matsumoto et al, 1992a, b;Moghul et al, 1994;Tamura et al, 1993) in a variety of tissues under physiological and pathological conditions. Among the regulatory molecules, injurin, which is produced by injured organs, is known to influence HGF/ SF gene expression (Matsumoto et al, 1992a). One Mars et al, 1993;Miyazawa et al, 1993;Shimomura et al, 1995); these are serum proteases, such as blood coagulation factor XIIa and its homologous protein named HGF-activator, and the urokinase-type plasminogen activator (uPA).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that expression of HGF and HGF receptor is regulated by different mechanisms. Considering the regulation of H G F expression, we recently found that injurin, a humoral factor which induces HGF-gene expression, appears to be involved in the induction of HGF following various organ injuries [46]. Kamalati et al found that HGF mRNA in MRC-5 human embryonic lung fibroblasts is strongly suppressed under heterotypic co-culture with several types of epithelial cells [47].…”
Section: Discussionmentioning
confidence: 99%